PERLUASAN FRASE DALAM CERPEN DAGANG CANANG - Adi Upadana, I Wayan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
Linguistics is the study of language. Balinese is the language used by Balinese people to communicate. Language is also used in pouring a sense of human art such as making a literary work. This study examines the use of grammar in a literary work. The object of research is phrases. A phrase is a construction built by constituents with various categories or classes of words. There are many variations that will be formed in a phrase. As a research subject, we use a short story entitled Dagang Canang. Based on data analysis, the expansion of Balinese phrases in the short story Dagang Canang includes: Noun phrase to the left Conj+N+N, Adj+N, Adj+N+N, Adv+N+N. Noun phrases to the right N+Adverb, N+N+Adj, N+Num, N+Adj. The noun phrases to the left and right have the pattern Verb+N+Num. Verbal phrases to the left Conj+V, Adverb+V, N+V, Pronomia+V. Verbal phrases to the right V+N, V+Pronouns. Verbal phrases to the left and right N+Verb+Adverb.